Early CSF and Serum S100B Concentrations for Outcome Prediction in Traumatic Brain Injury and Subarachnoid Hemorrhage - Kellermann, Isabel; Kleindienst, Andrea; Hore, Nirjhar; Buchfelder, Michael; Brandner, Sebastian (Clinical Neurology and Neurosurgery, 2016)
OBJECTIVES: S100B has been proposed as a putative biochemical marker in determining the extent of brain injury and corresponding prognosis in neurotrauma. The aim of this study was to evaluate the prognostic value of S100B early concentrations in serum and cerebrospinal fluid (CSF) in traumatic brain injury (TBI) and subarachnoid hemorrhage (SAH), to determine prognostically relevant threshold values and to evaluate fluctuation following EVD placement. PATIENTS AND METHODS: In 102 patients (45 SAH and 57 TBI) under intensive care unit (ICU) treated between January 2011 and December 2012 with external ventricular drain (EVD) S100B measurements were performed simultaneously in serum and CSF during the first 5 days and before and after EVD exchange. Glasgow coma scale (GCS) was assessed on admission and Glasgow outcome scale (GOS) 6 months later. RESULTS: Peak S100B levels in CSF and serum were measured on the first day after admission and concentrations decreased during the ensuing days post injury gradually. CSF and serum S100B concentrations in TBI patients were significantly higher than in SAH (p<0.005). Both in TBI and SAH patients S100B concentrations in CSF and serum were significantly higher in patients with an unfavorable outcome (GOS 1-3) in comparison to patients with a good outcome (GOS 4-5). Correlation of S100B concentrations in serum and GOS score at 6 months was significant both in TBI and SAH (p<0.05). Serum S100B concentrations >0.7μg/l correlated with 100% mortality. Correlation between S100B in CSF and GOS was significant in SAH (p<0.05), whereas it was not significant in TBI. After EVD exchange (n=53) we found a significant increase of S100B concentration in CSF (p<0.005). CONCLUSION: Initial S100B levels have a limited prognostic value in neurotrauma with CSF concentrations being highly sensitive to smallest influences like EVD placement. However, high initial S100B levels of >0.7μg/dl in serum are associated with 100% mortality, which might help to guide therapy strategies in severe neurotrauma.
EVALuna2:33856